MSME Empowerment through the Mukbang (Helping MSMEs Rise) Program: Case Study of Grandma Neng - Agus Purnomo; Masthuroh; Nety Kumalasari; Amelia Anwar; Muhammad Hafidz Khusnadin (PT Pustaka Cendekia Publisher, 2025)
The Mukbang program implemented at Pasar Kertapati, Palembang, aims to empower Micro, Small, and Medium Enterprises (MSMEs) by addressing key challenges in enhancing product visibility through more effective branding and marketing strategies. This study employs a qualitative descriptive case study approach, featuring the participation of Grandma Neng, a traditional vendor, in the program. The findings indicate significant improvements in product appeal and customer engagement, driven by interventions that included packaging enhancements, provision of promotional materials, and skills training sessions. While these positive results highlight the success of community-based approaches, the study also acknowledges limitations in terms of generalizability due to its focus on a single case. Future research is recommended to expand the program to include a broader range of MSMEs across different locations and to incorporate basic digital marketing training to enhance MSMEs' adaptability to changing market needs. These findings are expected to contribute to a broader discourse on MSME empowerment and economic development in Indonesia.